Multiplicity Results of Positive Radial Solutions for p-Laplacian Problems in Exterior Domains. (26th March 2008) - Kim, Chan-Gyun; Lee, Yong-Hoon; Sim, Inbo
Abstract : We find the second positive radial solution for the followingp -Laplacian problem:div ( | ∇ u | p − 2 ∇ u ) + K ( | x | ) u q = 0 inΩ, u | ∂ Ω = 0, u ( x ) → μ > 0 as| x | → ∞, whereΩ = x ∈ ℝ N : | x | > r 0 , r 0 > 0, N > p > 1, K ∈ C ( Ω, ( 0, ∞ ) ) andq > p − 1 . We also give some global existence results with respect to the parameterμ .